Acidaminococcus homini s sp. nov., Amedibacillus hominis sp. nov., Lientehia hominis gen. nov. sp. nov., Merdimmobilis hominis gen. nov. sp. nov., and Paraeggerthella hominis sp. nov., isolated from human faeces. Issue 2 (3rd February 2023) - Abdugheni, Rashidin; Li, Dan-Hua; Wang, Yu-Jing; Du, Meng-Xuan; Zhou, Nan; Liu, Chang; Liu, Shuang-Jiang
Abstract : The human gastrointestinal tract is inhabited by various microorganisms, including thousands of bacterial taxa that have yet to be cultured and characterized. In this report, we describe the isolation, cultivation, genotypic and phenotypic characterization and taxonomy of five novel anaerobic bacterial strains that were recovered during the massive cultivation and isolation of gut microbes from human faecal samples. On the basis of the polyphasic taxonomic results, we propose two novel genera and five novel species. They are Acidaminococcus hominis sp. nov. (type strain NSJ-142 T =CGMCC 1.17903 T =KCTC 25346 T ), Amedibacillus hominis sp. nov. (type strain NSJ-176 T =CGMCC 1.17933 T =KCTC 25355 T ), Lientehia hominis gen. nov. sp. nov. (type strain NSJ-141 T =CGMCC 1.17902 T =KCTC 25345 T ), Merdimmobilis hominis gen. nov. sp. nov. (type strain NSJ-153 T =CGMCC 1.17915 T =KCTC 25350 T ) and Paraeggerthella hominis sp. nov. (type strain NSJ-152 T =CGMCC 1.17914 T =KCTC 25349 T ).